Dyspepsia and personality traits among adult patients with headache: A single centre study / Anand Raj Silveraju - Anand Raj, Silveraju (2017)
Introduction: Headache and dyspepsia are commonly present among Malaysians. They may have different personality traits. We conducted a study to evaluate the frequency of dyspepsia in the patients with primary headache in University Malaya Medical Centre (UMMC). The secondary objective was to assess the various types of personality traits in the patients with headache and dyspepsia. Methodology: A cross sectional study wa conducted in then urom dical clinic. Demographic and headache characteristics were collected from the patients with migraine and tensiontype headache (TTH). Visual Analogue Scale (VAS) was used to determine the severity of the headache. Presence of dyspepsia was evaluated with Leeds questionnaire (LDQ). Minnesota Multiphasic Personality lnventory-2 restructured form (MMPI-2RF) questionnaire was used to assess the personality trait. Results: 60 patients with mean age 47.58±16.63 years were recruited. The patients were predominantly females (80%). The ethnic distribution was: Malay (31.7%), Chinese (28.3%) and Indians (40.0%). The headache subtype were: migraine without aura (n=l7, 28.3%), migraine with aura (n=14, 23.3%), frequent TTH (n=14, 23.3%), chronic TTH (n=l2, 20.0%) and infrequent TTH (n=3, 5.0%). 55% of the headache patients had dyspepsia. On univariate analysis migraine was more likely to be associated with dyspepsia compared to TTH (71 % migraine vs 37.9% TTH, p=0.019). Only 20 completed MMPI results were available for analysis. There was no statistical significance between headache with dyspepsia group/headache alone group with the five personality traits on MMPI. Conclusion: Migraine was more likely to be associated with dyspepsia compared to TTH. Personality trait associations among adults with headache and dyspepsia could not be demonstrated in this study.